Experiences of Every Mind Matters, Public Health England's adult mental health literacy campaign: a qualitative interview study - Ruth Stuart; Prisha Shah; Rachel Rowan Olive; Kylee Trevillion; Claire Henderson (BMC, 2023)
Abstract Background Every Mind Matters (EMM) is a publicly funded health campaign, launched in England in 2019, to equip adults to look after their mental health, and that of others, by offering online information about common problems: anxiety, low mood, sleep, and stress. This study is one component of an independent evaluation of EMM conducted by the NIHR Mental Health Policy Research Unit. Its aim is to explore individuals' experiences of the EMM campaign and website. Methods Four researchers, including three with lived experience of using mental health services, conducted 20, one-off, semi-structured, online interviews with a range of adult participants, including a sample of EMM users and a purposively recruited sub-sample known to have severe or long-term mental health conditions. A codebook thematic analysis was undertaken, and four main themes were identified. Findings There was an expectation from the name Every Mind Matters that its advice would address everyone. Almost all participants had experience of mental distress and looked to EMM for help with a current problem for themselves. All participants were complimentary about the EMM website and found it to be user-friendly (theme 1) and personalised (theme 2) especially the interactive feature Your Mind Plan quiz which responds with suggested actions to improve wellbeing and follows up with reminder emails. A few participants found the website information and/or Mind Plan suggestions to be life changing. Some participants wanted EMM to better acknowledge the contexts in which they live (theme 3) such as the limitations of health conditions and health services, and difficulties of crowded housing, social policy, and climate change. Many participants would like EMM to do more (theme 4), offer more interactivity, more choice, more information about available treatments, and more stratified advice to cover more severe mental health conditions. Conclusion EMM is available to all, including people with common or severe mental disorders. In the context of overwhelmed mental health services, people with severe mental illness expect more from EMM than advice about common problems. EMM could build on its success by extending its remit to address a wider range of needs so that everyone is included.